(3eGOI GdMjGI hMaX GdfaS ef GdBaGJs - (3eMeO Hf CHj HcQ Hf eMeO Hf MSf Hf Ydj GdaGQSj , HOQ GdOjf CHh YHO Gddg,J (B677 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3OYJfi GdYfGjI HMce GdeYJGO Cf CDda QSGdI TQjaI hSejJgG eGOI GdMjGI hMaX GdfaS ef GdBaGJ hLYdJgG eTJedI Ydi SHYI YTQ HGHkG s
(3BNQgG (B:s
(3hef CQGO Gdhbha Ydi NhGU GdChbGb , hTQGFW cJGHJgG adjWGdY GdcJGH GdPi CdafGg GdeSei BjGJ GdBaGJ aj NhGU GdChbGa s
(3GfXQ agQS GdWH HQbe (B"212-213" (3eGOI GdMjGI ai YdGbGJ LejY GdCTjGA GdeSeheI(B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B213 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH JjehQ (B134) s
Keywords: (3GdWHs